FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM PEMBIAYAAN CICIL EMAS DI BANK SYARIAH INDONESIA KC. ROGOJAMPI - Rahmad Hendi Zaelani (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2022)
The value of the benefits of gold can be emotionally enjoyed in its beauty, gold as a precious metal with a high aesthetic value, as one of the profitable investments and continues to move up to its price specifications. The added value that gold has as a symbol of glory and social status for everyone who has. These values encourage Bank Syariah Indonesia to create gold installment products to help customers to finance the purchase / ownership of precious metal gold or lantakan in a very easy and profitable way. This research is with a qualitative approach, phenomenology study to customers of Bank Syariah Indonesia KC. Rogojampi. The results showed that the customer's decision to make a purchase or financing of gold installments at Bank Syariah Indonesia KC. Rogojampi because of four factors, namely service factors on the part of banking employees, social factors for the usefulness of products, personal factors to get the essence value of the company. Keywords: Customer Decision, Gold Installment Financing